Cytokines and Myelination in the Central Nervous System - Thomas Schmitz; Li-Jin Chew (The Scientific World Journal)
Myelin abnormalities that reflect damage to developing and mature brains are often found in neurological diseases with evidence of inflammatory infiltration and microglial activation. Many cytokines are virtually undetectable in the uninflamed central nervous system (CNS), so that their rapid induction and sustained elevation in immune and glial cells contributes to dysregulation of the inflammatory response and neural cell homeostasis. This results in aberrant neural cell development, cytotoxicity, and loss of the primary myelin-producing cells of the CNS, the oligodendrocytes. This article provides an overview of cytokine and chemokine activity in the CNS with relevance to clinical conditions of neonatal and adult demyelinating disease, brain trauma, and mental disorders with observed white matter defects. Experimental models that mimic human disease have been developed in order to study pathogenic and therapeutic mechanisms, but have shown mixed success in clinical application. However, genetically altered animals, and models of CNS inflammation and demyelination, have offered great insight into the complexities of neuroimmune interactions that impact oligodendrocyte function. The intracellular signaling pathways of selected cytokines have also been highlighted to illustrate current knowledge of receptor-mediated events. By learning to interpret the actions of cytokines and by improving methods to target appropriate predictors of disease risk selectively, a more comprehensive understanding of altered immunoregulation will aid in the development of advanced treatment options for patients with inflammatory white matter disorders.